Cellular Uptake of Catharanthus roseus-Silver Nanoparticles in Human Hepatocellular Carcinoma HepG2 Cells - Nur Asna Azhar; Siti Aishah Abu Bakar; Siti Hawa Ngalim; Nor Hazwani Ahmad (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Nanoparticles exhibit unique features and currently at the forefront of cutting-edge research. Silver nanoparticles (AgNPs) are among the most promising and widely commercialised nanoproducts in various fields. The interaction of these AgNPs with cells remain unclear to connect with its toxicological endpoints. The aim of this study was to investigate the cellular uptake of C. roseus-AgNPs in hepatocellular carcinoma cells HepG2. Methods: The HepG2 cells were treated with the mean IC50 value of C. roseus-AgNPs which was 4.95±0.26 μg/mL for 24, 48 and 72 hours. The effects were compared with the untreated cells and other treatments which include camptothecin, C. roseus-aqueous extract, and AgNO3. Inductively coupled plasma optical emission spectroscopy (ICP-OES) was used to quantify the intracellular Ag+ and Ca2+, while transmission electron microscopy (TEM) imaging was used to visualise the nanoparticle distribution. Results: The HepG2 cells have significantly taken up Ag+ from C. roseus-AgNPs with at least six times higher compared to Ag+ from AgNO3. The intracellular Ca2+ detected in HepG2 cells for all treatments were significantly higher than the untreated cells, in time-dependent manner. TEM images indicated the endocytosis of C. roseus-AgNPs with the presence of endosomes and exocytic vesicles. Conclusion: The significant accumulation of intracellular Ag+ demonstrated the efficiency of the C. roseus-AgNPs uptake while the increased Ca2+ indicated the early sign of cell injury. The cellular uptake was mainly through endocytosis. These findings are crucial to correlate the physicochemical properties of C. roseus-AgNPs with the anticancer mechanisms towards the development of liver cancer therapy. REFERENCE Piao MJ, Kang KA, Lee IK, Kim HS, Kim S, Choi JJYJ, et al. Silver nanoparticles induce oxidative cell damage in human liver cells through inhibition of reduced glutathione and induction of mitochondria- involved apoptosis. Toxicol Lett [Internet]. 2011 Feb 25 [cited 2018 Mar 25];201(1):92–100. doi:10.1016/j.toxlet.2010.12.010 Huang Y, He L, Liu W, Fan C, Zheng W, Wong YS, et Selective cellular uptake and induction of apoptosisofcancer-targetedseleniumnanoparticles. Biomaterials [Internet]. 2013;34(29):7106–16. Adoi:10.1016/j.biomaterials.2013.04.067 Khorrami S, Zarrabi A, Khaleghi M, Danaei M, Mozafari MR. Selective cytotoxicity of green synthesized silver nanoparticles against the MCF-7 tumor cell line and their enhanced antioxidant and antimicrobial properties. Int J Nanomedicine [Internet]. 2018 [cited 2020 Sep 1];13:8013–24. Available from: /pmc/articles/ PMC6267361/?report=abstract Fröhlich E. The role of surface charge in cellular uptake and cytotoxicity of medical nanoparticles [Internet]. Vol. 7, International Journal of Nanomedicine. Dove Press; 2012 [cited 2019 Feb 20]. p. 5577–91. Available from: http://www.ncbi. nih.gov/pubmed/23144561 Kapara A, Brunton V, Graham D, Faulds K. Investigation of cellular uptake mechanism of functionalised gold nanoparticles into breast cancer using Chem Sci. 2020;11(22):5819–doi: 10.1039/D0SC01255F Chithrani BD, Chan WCW. Elucidating the mechanism of cellular uptake and removal of protein-coated gold nanoparticles of different sizes and Nano Lett [Internet]. 2007 [cited 2018 May 3];7(6):1542–50. doi:10.1021/nl070363y Loutfy SA, Al-Ansary NA, Abdel-Ghani NT, Hamed AR, Mohamed MB, Craik JD, et al. Anti- proliferative activities of metallic nanoparticles in an in vitro breast cancer Asian Pacific J Cancer Prev. 2015;16(14):6039–46. doi: 10.7314/ apjcp.2015.16.14.6039. Maduraiveeran G, Sasidharan M, Ganesan V. Electrochemical sensor and biosensor platforms based on advanced nanomaterials for biological and biomedical Vol. 103, Biosensors and Bioelectronics. Elsevier Ltd; 2018. p. 113–29. doi: 10.1016/j.bios.2017.12.031 Ghozali SZ, Ismail MN & Ahmad NH. Characterisation of Silver Nanoparticles using a Standardised Catharanthus roseus Aqueous Malaysian Journal of Medicine and Health Sciences 2018;14(SUPP1):120–125 Azhar NA, Ghozali SZ, Abu Bakar SA, Lim V, Ahmad NH. Suppressing growth, migration, and invasion of human hepatocellular carcinoma HepG2 cells by Catharanthus roseus-silver nanoparticles. Toxicol Vitr. 2020 Sep 1;67(10):4910. doi: 10.1016/j. tiv.2020.104910. AshaRani P V., Hande MP, Valiyaveettil S. Anti- proliferative activity of silver nanoparticles. BMC Cell Biol [Internet]. 2009 Sep 17 [cited 2020 Sep 28];10(1):65. doi:10.1186/1471-2121-10-65 Fröhlich E. The role of surface charge in cellular uptake and cytotoxicity of medical nanoparticles [Internet]. Vol. 7, International Journal of Dove Press; 2012 [cited 2022 Sep 18]. p. 5577–91. Available from: /pmc/articles/ PMC3493258/ Ghozali SZ, Vuanghao L Biosynthesis and Characterization of Silver Nanoparticles using Catharanthus roseus Leaf Extract and its Proliferative Effects on Cancer Cell Lines. J Nanomed Nanotechnol. 2015;06(04):1–10. doi: 10.4172/2157-7439.1000305 Wu M, Guo H, Liu L, Liu Y, Xie Size-dependent cellular uptake and localization profiles of silver nanoparticles. Int J Nanomedicine [Internet]. 2019 [cited 2022 Sep 16];14:4247–59. doi: doi: 10.2147/IJN.S201107 Guo H, Zhang J, Boudreau M, Meng J, Yin J jie, Liu J, et al. Intravenous administration of silver nanoparticles causes organ toxicity through intracellular ros-related loss of interendothelial junction. Part Fibre Toxicol [Internet]. 2016 Apr 29 [cited 2022 Sep 14];13(1). doi: 1186/s12989-016-0133-9. Verma A, Stellacci Effect of Surface Properties on Nanoparticle–Cell Interactions. Small [Internet]. 2010 Jan 4 [cited 2022 Sep 13];6(1):12–21. doi:10.1002/smll.200901158 Albanese A, Tang PS, Chan The Effect of Nanoparticle Size, Shape, and Surface Chemistry on Biological Systems. Annu Rev Biomed Eng 2012 [Internet]. 2012 [cited 2022 Sep 16];14:1–16. doi: 10.1146/annurev-bioeng-071811-150124. Ghozali SZ, Ismail MN, Ahmad NH. Characterisation of Silver Nanoparticles using a Standardised Catharanthus roseus Aqueous Extract. Malaysian J Med Heal 2018;14(SUPP1):120– 5. Foroozandeh P, Aziz AA. Insight into Cellular Uptake and Intracellular Trafficking of Nanoparticles [Internet]. Vol. 13, Nanoscale Research Nanoscale Res Lett; 2018 [cited 2022 Sep 18]. doi: doi: 10.1186/s11671-018-2728-6. Brkić Ahmed L, Milić M, Pongrac IM, Marjanović AM, Mlinarić H, Pavičić I, et al. Impact of surface functionalization on the uptake mechanism and toxicity effects of silver nanoparticles in HepG2 cells. Food Chem 2017;107:349–61. doi: 10.1016/j.fct.2017.07.016 Wang Z, Li N, Zhao J, White JC, Qu P, Xing CuO nanoparticle interaction with human epithelial cells: Cellular uptake, location, export, and genotoxicity. Chem Res Toxicol [Internet]. 2012 Jul 16 [cited 2022 Sep 18];25(7):1512–21. doi: 10.1021/tx3002093 Meindl C, Kueznik T, Bösch M, Roblegg E, Fröhlich E. Intracellular calcium levels as screening tool for nanoparticle toxicity. J Appl Toxicol [Internet]. 2015 Oct 1 [cited 2022 Sep 18];35(10):1150–9. doi:10.1002/jat.3160 AshaRani P V., Mun GLK, Hande MP, Valiyaveettil S. Cytotoxicity and genotoxicity of silver nanoparticles in human cells. ACS Nano [Internet]. 2009 Feb 24 [cited 2022 Sep 11];3(2):279–90. doi: 10.1021/nn800596w. Chinopoulos C, Adam-Vizi V. Calcium, mitochondria and oxidative stress in neuronal pathology: Novel aspects of an enduring theme [Internet]. Vol. 273, FEBS Journal. FEBS J; 2006 [cited 2020 Nov 19]. p. 433–50. doi: 10.1111/j.1742-4658.2005.05103.x. Moutin MJ, Abramson JJ, Salama G, Dupont Y. Rapid Ag+-induced release of Ca2+ from sarcoplasmic reticulum vesicles of skeletal muscle: a rapid filtration study. BBA - Biomembr [Internet]. 1989 Sep 18 [cited 2022 Sep 11];984(3):289–92. doi: 10.1016/0005-2736(89)90295-2. Orrenius S, McCabe MJ, Nicotera P. Ca2+- dependent mechanisms of cytotoxicity and programmed cell death. Toxicol Lett [Internet]. 1992 [cited 2022 Sep 11];64–65(C):357–64. doi: 10.1016/0378-4274(92)90208-2. Hsu YL, Kuo PL, Cho CY, Ni WC, Tzeng TF, Ng LT, et al. Antrodia cinnamomea fruiting bodies extract suppresses the invasive potential of human liver cancer cell line PLC/PRF/5 through inhibition of nuclear factor κB pathway. Food Chem Toxicol [Internet]. 2007 Jul 1 [cited 2018 Apr 10];45(7):1249–57. doi: 10.1016/j.fct.2007.01.005 Milić M, Leitinger G, Pavićić I, Avdičević Z, Dobrović S, Goessler W, et al. Cellular uptake and toxicity effects of silver nanoparticles in mammalian kidney cells. J Appl Toxicol [Internet]. 2014 Jun [cited 2018 Mar 28];35(6):581–92. doi: 10.1002/jat.3081. Brandenberger C, Mühlfeld C, Ali Z, Lenz AG, Schmid O, Parak WJ, et al. Quantitative evaluation of cellular uptake and trafficking of plain and polyethylene glycol-coated gold nanoparticles. Small [Internet]. 2010 Jul 2 [cited 2020 Oct 28];6(15):1669–78. doi:10.1002/smll.201000528 Gliga AR, Skoglund S, Odnevall Wallinder I, Fadeel B, Karlsson HL. Size-dependent cytotoxicity of silver nanoparticles in human lung cells: The role of cellular uptake, agglomeration and Ag release. Part Fibre Toxicol [Internet]. 2014 Feb 17 [cited 2020 Nov 10];11(1):11. doi:10.1186/1743-8977-11-11